Phylogeny and taxonomy of the scab and spot anthracnose fungus Elsinoë (Myriangiales, Dothideomycetes) - X. L. Fan (2018)
© 2017 Westerdijk Fungal Biodiversity Institute Species of Elsinoë are phytopathogens causing scab and spot anthracnose on many plants, including some economically important crops such as avocado, citrus, grapevines, and ornamentals such as poinsettias, field crops and woody hosts. Disease symptoms are often easily recognisable, and referred to as signature-bearing diseases, for the cork-like appearance of older infected tissues with scab-like appearance. In some Elsinoë-host associations the resulting symptoms are better described as spot anthracnose. Additionally the infected plants may also show mild to severe distortions of infected organs. Isolation of Elsinoë in pure culture can be very challenging and examination of specimens collected in the field is often frustrating because of the lack of fertile structures. Current criteria for species recognition and host specificity in Elsinoë are unclear due to overlapping morphological characteristics, and the lack of molecular and pathogenicity data. In the present study we revised the taxonomy of Elsinoë based on DNA sequence and morphological data derived from 119 isolates, representing 67 host genera from 17 countries, including 64 ex-type cultures. Combined analyses of ITS, LSU, rpb2 and TEF1-α DNA sequence data were used to reconstruct the backbone phylogeny of the genus Elsinoë. Based on the single nomenclature for fungi, 26 new combinations are proposed in Elsinoë for species that were originally described in Sphaceloma. A total of 13 species are epitypified with notes on their taxonomy and phylogeny. A further eight new species are introduced, leading to a total of 75 Elsinoë species supported by molecular data in the present study. For the most part species of Elsinoë appear to be host specific, although the majority of the species treated are known only from a few isolates, and further collections and pathogenicity studies will be required to reconfirm this conclusion.